Substantiation of the Escalator Tunnel Construction Technology Based on the Results of Field Research - Bielikova, S. I.; Tiutkin, O. L. (Science and Transport Progress, 2023)
Purpose. The authors aim to substantiate a new technology for the construction of an escalator tunnel in Ukraine based on the results of field studies performed as part of surveying measurements during the construction of the inclined run of the Dnipro metro. Methodology. The article analyzes the main technology of the escalator tunnel construction, which was based on the development of an inclined working from top to bottom with preliminary preparation of the massif by means of artificial soil freezing. Several cases of application of the bottom-up escalator tunnel construction method using the New Austrian Tunneling Method (NATM), which is successfully used in metro of other countries, are considered. The main principle of the method is that a shotcrete system is used as a temporary (primary) support, and a reinforcement system with monolithic concrete is used as a permanent support. Findings. The authors analyzed the peculiarities of the escalator tunnel excavation of the Dnipro metro by the Turkish company «Limak» in 2017–2018. It was noted that the excavation was carried out from the bottom up in conditions of strong rock (plagiogranite) using drilling and blasting operations. The characteristic results of field studies during drilling and blasting operations in the process of developing the calotte are analyzed. On the basis of these data, it is possible to trace the tendency to the appearance of minor overburden during sinking. The value of the deformed state (displacement of the contour of the designed casing) is within the normative limits, which indicates the effective use of these works within the framework of NATM. It is proved that in the conditions of military operations, the technology of building an escalator tunnel from the bottom up is a guarantee of the safety of workers and equipment. Originality. The results of the scientific work presented in the article make it possible to determine the level of deformed state during the excavation of the escalator tunnel of the Dnipro metro in hard rocks. During the field studies, the dependences of deformation of plagiogranite in the inclined bore were obtained. Practical value. An alternative technology for the construction of a bottom-up escalator tunnel based on NATM with the provision of normative deformation of the surrounding rock mass is substantiated.